2020
DOI: 10.1088/2053-1591/ab6ad5
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the silicon solar cell efficiency with transition metal oxide nano-thin films as anti-reflection coatings

Abstract: Herein, we report the study on RF-sputtered transition metal oxide thin films of Zinc oxide, Magnesium oxide, and Aluminum oxide as an antireflection coating on silicon-based solar cells and their influence on energy conversion. The transmission spectrum of all sputtered metal oxides was studied using a UV-visible spectrophotometer. The phase formation and microstructure analysis of these sputtered oxides were studied using glass for the destructive test along with the device. The x-ray diffraction and cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…In this context, the XPS spectrum of Ag@ZnO core-shell nanoparticles is shown in Figure 2. Similar to the other studies 50 the full spectrum confirmed the presence of Zn, Ag, O, and C in the structure. Therefore, it is established that these elements exist in the structure.…”
Section: Resultssupporting
confidence: 89%
“…In this context, the XPS spectrum of Ag@ZnO core-shell nanoparticles is shown in Figure 2. Similar to the other studies 50 the full spectrum confirmed the presence of Zn, Ag, O, and C in the structure. Therefore, it is established that these elements exist in the structure.…”
Section: Resultssupporting
confidence: 89%
“…Such solar cells could be utilized to cover windows in buildings and produce electricity without blocking indoor space access to light since the refractive index of metal oxides is mainly between the refractive index of silicon and air. They can also be utilized as an anti-reflection coating layer for other silicon solar cell devices [ 6 ]. Furthermore, metal oxides are widely used as an electron transport layer (ETL) and hole transport layer (HTL) in perovskite-based solar cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…That is why various types of thin-film anti-reflective (AR) coatings are used to lower this reflection loss but these AR coatings also have limits to absorb a certain light spectrum. In addition, there are some disadvantages on using the AR coating, such as thermal and adhesive mismatch with the substrates, which requires a specific choice of material and geometry [4][5][6][7]. Figure 1 represents a glimpse of various solar cells, the basic concept, and relation of the light guiding towards light trapping into nano-structures.…”
Section: Background Motivation and Performed Workmentioning
confidence: 99%